P13 T2 biomarker-guided oral corticosteroid weaning in asthma. (11th November 2022) - Thomson, LA; Hearn, AP; Lam, JL; Fernandes, M; Green, LM; Roxas, C; D'Anconna, G; Dhariwal, J; Nanzer, AM; Jackson, DJ
Abstract : Introduction: It has been recognised for several decades that oral corticosteroids (OCS) offer little benefit in the absence of eosinophilic/T2 airways inflammation, yet guidelines continue to suggest a symptom-based rather than biomarker-based approach to asthma treatment leading to many patients inappropriately escalated to maintenance (m)OCS for symptoms that relate to co-morbid pulmonary and/or extrapulmonary conditions. Our tertiary asthma unit runs a nurse-led clinic specifically for patients referred on mOCS lacking any objective evidence of T2 inflammation to guide OCS-weaning according to T2 biomarkers and prevent ongoing avoidable harm due to the adverse effects of systemic steroids. Methods: We conducted a retrospective review of patients referred on mOCS without evidence of T2 airways inflammation (FeNO<25ppb AND blood eosinophils<0.3) to report the outcome of a biomarker-led rather than symptom-led OCS weaning approach. Patients were seen every 1–4 weeks with FeNO, blood eosinophil count, spirometry, and ACQ6 recorded at each visit. OCS dose was progressively weaned if the biomarkers remained in the normal range. Results: Twenty-four patients (mean age 45, 83% female) were identified who had been referred on long-standing mOCS (median duration 54 months [IQR 24–150]) despite an absence of objective T2 inflammation. The median OCS dose was 15.5 mg (IQR 10–25 mg) prednisolone. 13/24 (54%) were obese with a mean BMI of 38. 11/24 (45.8%) had a dysfunctional breathing pattern, 9/24 (37.5%) had severe GORD and 9/25 (37.5%) had laryngeal dysfunction (37.5%). 70% of patients were able to wean off mOCS for their asthma by 8 weeks, and 90% by 12 weeks. ACQ-6 did not differ significantly from baseline (3.16 ± 1.09) to week 8 (mean 3.36 ± 1.08). 17/24 (71%) did not have any evidence of T2 inflammation once off mOCS for their asthma. The remaining 7/24 patients did subsequently develop evidence of T2 airways inflammation despite high dose ICS. There were no adverse outcomes related to the OCS wean. Conclusion: Many patients are inappropriately treated with mOCS for symptoms driven by extrapulmonary co-morbidities. Our results demonstrate that such patients can be safely weaned off mOCS using a T2 biomarker-based rather than symptom-based approach reducing avoidable steroid-related harm to patients.